2011
DOI: 10.1111/j.1752-9824.2011.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge of osteoporosis and self-efficacy perception of female orthopaedic patients in Turkey

Abstract: Ozturk a & Sendirm(2011) Journal of Nursing and Healthcare of Chronic Illness3, 319–328 
Evaluation of knowledge of osteoporosis and self‐efficacy perception of female orthopaedic patients in Turkey Aim.  To evaluate the osteoporosis knowledge and self‐efficacy of female orthopaedic patients. Background.  Osteoporosis can affect either gender; however, 80% of those affected are women. Many women present with fractures of the hip or wrist each year as a result of osteoporosis. The disease is essentially incurab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
2
22
0
3
Order By: Relevance
“…The majority of women had modest knowledge on osteoporosis. Younger women were at increased risk for low bone mass and premature osteoporosis [6] .  Majority of the pre menopausal women 16 (32%) were in the age group of 45-50 years, 14 (28%) were in the age group of 56-60, 11(22%) were in the age group of 61-65 years and 9(18%) in the age group of 51-55 years.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of women had modest knowledge on osteoporosis. Younger women were at increased risk for low bone mass and premature osteoporosis [6] .  Majority of the pre menopausal women 16 (32%) were in the age group of 45-50 years, 14 (28%) were in the age group of 56-60, 11(22%) were in the age group of 61-65 years and 9(18%) in the age group of 51-55 years.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted with women in Turkey showed a linear relation between the years of education and osteoporosis self-efficacy level (23). In addition, age was found to be related to the osteoporosis knowledge and osteoporosis self-efficacy of women (24). The OKT-tot and OKT-exc scores of the working women were 3.8 and 3.2 times higher than those of the housewives, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Farkındalık ve bilgi düzeyinin günlük yaşamda eyleme dönüştürülebilmesindeki eksikliği gösteren bu sonuç ayrıca araştırılmaya değer görülmektedir. OBT'nin Türkçe geçerlilik ve güvenilirliğinin yapılmasını takiben yine ülkemizde yapılan, ortopedi kliniklerine başvurmuş çoğunluğu postmenopozal kadın hastalarda, OBT skorlarının oldukça düşük olduğu [beslenme alt grubu ortalaması 6,5 (maksimum 14), egzersiz alt grubu ortalaması 6 (maksimum 14), toplam skor ortalaması 9,9 (maksimum20)] tespit edilmiştir (25). Hemşirelik öğrencilerinin bilgi düzeyinin araştırıldığı bir diğer çalışmada ise OBT toplam skor ortalaması 13 olduğu, öğrencilerin %75,4'ünün tavsiye edilen miktarda kalsiyum almadığı, %51,2'sinin ise egzersiz yapmadığı belirlenmiştir (26).…”
Section: Discussionunclassified